2016
DOI: 10.1111/coa.12672
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of outcome by lymph node ratio in patients with parotid gland cancer

Abstract: After surgery for PGC, evaluation of the neck using LNR was found to reliably stratify the overall survival rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 24 publications
4
17
0
Order By: Relevance
“…The role of LNR as an independent prognostic factor for OS has also been reported in other studies . The cutoff values for LNR that were used to stratify the risk of major SGC patients have varied from a range of 11% to 38% in different studies . Considering that LNR is a ratio of PLNs/ELNs, PLNs count has also demonstrated a significant role as prognostic indicator as expected.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The role of LNR as an independent prognostic factor for OS has also been reported in other studies . The cutoff values for LNR that were used to stratify the risk of major SGC patients have varied from a range of 11% to 38% in different studies . Considering that LNR is a ratio of PLNs/ELNs, PLNs count has also demonstrated a significant role as prognostic indicator as expected.…”
Section: Discussionsupporting
confidence: 66%
“…Moreover, it showed that the <5 NLNs count was significant as compared to >12 NLNs count only. The role of LNR as an independent prognostic factor for OS has also been reported in other studies . The cutoff values for LNR that were used to stratify the risk of major SGC patients have varied from a range of 11% to 38% in different studies .…”
Section: Discussionmentioning
confidence: 58%
“…7 LNR emerged as an important additional predictor in multiple entities and locations of carcinomas. 6,12,13 In comparison with the UICC/AJCC and were shown to have a worse prognosis in comparison with HPVpositive OPSCC. 3,[19][20][21] The worse response of HPV-negative OPSCC to radiotherapy and chemotherapy was assumed to be the reason.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical lymph node status is one of the most important, well‐known predictors of prognosis in head and neck cancer in general . LNR emerged as an important additional predictor in multiple entities and locations of carcinomas . In comparison with the UICC/AJCC TNM classification, represented by seven categories with regard to the pN categories (pN0, pN1, pN2a, pN2b, pN2c, pN3a and pN3b), the LNR provides a metric scale.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation